PENGATURAN KECEPATAN PUTARAN MOTOR DC BERBASIS KOMPUTER - Anshori, Yusuf (MEKTEK, 2009)
The development of industrial world needs an instrumentation automation that to support production process. For a true intelligent and flexible automated manufacturing system, the system should be able to respond to changing conditions by changing the manufacturing process all by itself. Computers can be programmed to "read" external conditions and to execute different parts of their programs depending on the sensed conditions. Computers will require additional interface cards like PPI 8255 and programming like Delphi. Various excess and amenity high level programming language base on GUI (Graphical User Interface) and running at Windows Operating System like Delphi make a produce application more quicker and efficient. DC motor which is ordinary to be used as automation actuator can be controling movement by computer